Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases - Cardenas, Pablo D.; Sonawane, Prashant D.; Heinig, Uwe; Jozwiak, Adam; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Pliner, Margarita; Unger, Tamar; Wolf, Dalia; Ofner, Itai; Vilaprinyo, Ester; et al. (Nature Communications, 2019)
The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) enzymes catalyze SGA-hydroxylation across various Solanum species. In contrast to cultivated potato, Solanum chacoense, a widespread wild potato species, has evolved a 2-ODD enzyme leading to the formation of leptinines. Furthermore, we find a related 2-ODD in tomato that catalyzes the hydroxylation of the bitter a-tomatine to hydroxytomatine, the first committed step in the chemical shift towards downstream ripening-associated non-bitter SGAs (e.g. esculeoside A). This 2-ODD enzyme prevents bitterness in ripe tomato fruit consumed today which otherwise would remain unpleasant in taste and more toxic.

2-oxoglutarate-dependent dioxygenases drive expansion of steroidal alkaloid structural diversity in the genus Solanum - Sonawane, Prashant D.; Jozawiak, Adam; Barbole, Ranjit; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Gharat, Sachin A.; Ramot, Ofir; Unger, Tamar; Wizler, Guy; Meir, Sagit; Rogachev, Ilana; et al. (New Phytologist, 2022)
Solanum steroidal glycoalkaloids (SGAs) are renowned defence metabolites exhibiting spectacular structural diversity. Genes and enzymes generating the SGA precursor pathway, SGA scaffold and glycosylated forms have been largely identified. Yet, the majority of downstream metabolic steps creating the vast repertoire of SGAs remain untapped. Here, we discovered that members of the 2-OXOGLUTARATE-DEPENDENT DIOXYGENASE (2-ODD) family play a prominent role in SGA metabolism, carrying out three distinct backbone-modifying oxidative steps in addition to the three formerly reported pathway reactions. The GLYCOALKALOID METABOLISM34 (GAME34) enzyme catalyses the conversion of core SGAs to habrochaitosides in wild tomato S. habrochaites. Cultivated tomato plants overexpressing GAME34 ectopically accumulate habrochaitosides. These habrochaitoside enriched plants extracts potently inhibit Puccinia spp. spore germination, a significant Solanaceae crops fungal pathogen. Another 2-ODD enzyme, GAME33, acts as a desaturase (via hydroxylation and E/F ring rearrangement) forming unique, yet unreported SGAs. Conversion of bitter alpha-tomatine to ripe fruit, nonbitter SGAs (e.g. esculeoside A) requires two hydroxylations; while the known GAME31 2-ODD enzyme catalyses hydroxytomatine formation, we find that GAME40 catalyses the penultimate step in the pathway and generates acetoxy-hydroxytomatine towards esculeosides accumulation. Our results highlight the significant contribution of 2-ODD enzymes to the remarkable structural diversity found in plant steroidal specialized metabolism.
Keywords: Solanum; specialized metabolism; steroidal glycoalkaloids (SGAs); structural diversity; Tomato

Steroidal alkaloids defence metabolism and plant growth are modulated by the joint action of gibberellin and jasmonate signalling - Panda, Sayantan; Jozwiak, Adam; Sonawane, Prashant D.; Szymanski, Jedrzej; Kazachkova, Yana; Vainer, Andrii; Kilambi, Himabindu Vasuki; Almekias-Siegl, Efrat; Dikaya, Varvara; Bocobza, Samuel; Shohat, Hagai; Meir, Sagit; et al. (New Phytologist, 2022)
Steroidal glycoalkaloids (SGAs) are protective metabolites constitutively produced by Solanaceae species. Genes and enzymes generating the vast structural diversity of SGAs have been largely identified. Yet, mechanisms of hormone pathways coordinating defence (jasmonate; JA) and growth (gibberellin; GA) controlling SGAs metabolism remain unclear. We used tomato to decipher the hormonal regulation of SGAs metabolism during growth vs defence tradeoff. This was performed by genetic and biochemical characterisation of different JA and GA pathways components, coupled with in vitro experiments to elucidate the crosstalk between these hormone pathways mediating SGAs metabolism. We discovered that reduced active JA results in decreased SGA production, while low levels of GA or its receptor led to elevated SGA accumulation. We showed that MYC1 and MYC2 transcription factors mediate the JA/GA crosstalk by transcriptional activation of SGA biosynthesis and GA catabolism genes. Furthermore, MYC1 and MYC2 transcriptionally regulate the GA signalling suppressor DELLA that by itself interferes in JA-mediated SGA control by modulating MYC activity through protein-protein interaction. Chemical and fungal pathogen treatments reinforced the concept of JA/GA crosstalk during SGA metabolism. These findings revealed the mechanism of JA/GA interplay in SGA biosynthesis to balance the cost of chemical defence with growth.
Keywords: alpha-tomatine; defence; gibberellin (GA); growth; jasmonate (JA); steroidal glycoalkaloids (SGAs); Tomato

Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.